The Influence of Informativeness, Interactivity, and Electronic Word of Mouth in Social Media Marketing Strategy on Customer Satisfaction at Toba Caldera Resort - Diana Trisisca; Annisa Sanny; Erwansyah Erwansyah (Utan Kayu Publishing, 2025)
This research was conducted at Toba Caldera Resort to determine and analyze the influence of informativeness, interactivity, and electronic word of mouth (WOM) in social media marketing strategies on customer satisfaction at Toba Caldera Resort. The population in this study was visitors to Toba Caldera Resort. The sample was drawn using the Hair formula, and the sampling technique used non-probability sampling, as well as purposive sampling. The method used in this study was quantitative with an associative type. Data collection was carried out using a questionnaire and a Likert scale for variables. The data analysis tool was multiple linear regression using Statistical Package for the Social Sciences (SPSS) 25.0 software. The results showed that informativeness had a positive and significant effect on customer satisfaction, interactivity had a positive and significant effect on customer satisfaction, and electronic word of mouth had a positive and significant effect on customer satisfaction. The results of this study found that informativeness, interactivity, and electronic word of mouth simultaneously had a positive and significant effect on customer satisfaction at Toba Caldera Resort